2003
DOI: 10.1023/a:1021189505212
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Economic and political pressures have led state governments to shrink and close long-term psychiatric inpatient units in favor of community-based treatment. These pressures present inpatient clinicians with an opportunity to examine their clinical practices and question whether the focus of treatment addresses the behaviors most relevant to helping patients achieve discharge and maintain community tenure. The social learning approach of Gordon Paul is the empirically validated treatment of choice for long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In one study, the rates of aggressive and self-injurious behaviors were found to decrease on an SLP ward over time such that these behaviors were significantly lower than the rates found on traditional care wards (Bellus et al, 1999). Another report from the same facility found significant improvements over time among clients admitted into an SLP in self-care skills and treatment engagement, as measured by rates of attendance and successful participation in groups and classes (Bellus et al, 2003). That same report revealed that clients who did not achieve discharge were more likely to refuse to attend treatment groups and were more likely to engage in nonviolent problematic and dangerous behaviors (Bellus et al, 2003).…”
mentioning
confidence: 99%
“…In one study, the rates of aggressive and self-injurious behaviors were found to decrease on an SLP ward over time such that these behaviors were significantly lower than the rates found on traditional care wards (Bellus et al, 1999). Another report from the same facility found significant improvements over time among clients admitted into an SLP in self-care skills and treatment engagement, as measured by rates of attendance and successful participation in groups and classes (Bellus et al, 2003). That same report revealed that clients who did not achieve discharge were more likely to refuse to attend treatment groups and were more likely to engage in nonviolent problematic and dangerous behaviors (Bellus et al, 2003).…”
mentioning
confidence: 99%
“…a few studies used a treatment as usual comparison (owen, Sellwood, Kan, Murray, & Sarsam, 2015;rosner, Lumbeck, & geissner, 2011;veltro et al, 2008;Wykes, parr, & Landau, 1999). the rest compared before and after measurements to show positive results (Bellus et al, 2003;Chadwick et al, 2000;hodel & West, 2003;Long et al, 2016;Lynch, Berry, & Sirey, 2011;Manning, hooke, tannenbaum, Blythe, & Clarke, 1994;Mcinnis, Sellwood, & Jones, 2006;newton et al, 2005;pinkham, gloege, Flanagan, & penn, 2004;Wykes et al, 1999). Most were admittedly pilot programs.…”
Section: [Al Nods]mentioning
confidence: 99%
“…the scope of symptom acuity that responded positively to CBt group ranges from first break adolescents (newton et al, 2005) to chronic psychotic patients hospitalized for more than 2 years (Bellus et al, 2003). the studies suggested that a broad array of realistic goals is accomplished in CBt group.…”
Section: Symptoms and Goals Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations